Social Comparisons and Attitudes towards Foreigners - Evidence from the `Fall of the Iron Curtain' - Lutz Schneider; Walter Hyll (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
We exploit the natural experiment of German division and reunification to address the question whether individuals who feel distress from social comparisons in terms of income reveal more negative attitudes towards foreigners. Our empirical approach rests upon individuals from the German Democratic Republic, who have West German peers. We use the variation of wealth of West German peers shortly after the fall of the Berlin Wall in 1989 to identify a causal effect of distress from social comparisons among East Germans. We find robust evidence that East Germans expose strong negative attitudes towards foreigners if they worry about their economic status compared to better-off peers in West Germany. Our analysis also reveals that this adverse effect of upward social comparisons is more pronounced towards foreigners stemming from low-wage countries.
Keywords: J15; D63; Z13; 330